The Sulfate Supply Maximizing Arabidopsis Shoot Growth Is Higher under Long- than Short-Term Exposure to Cadmium - Ferri, Alessandro; Lancilli, Clarissa; Maghrebi, Moez; Lucchini, Giorgio; Sacchi, Gian Attilio; Nocito, Fabio F. (Frontiers in Plant Science, 2017)
The processes involved in cadmium detoxification in plants deeply affect sulfate uptake and thiol homeostasis and generate increases in the plant nutritional request for sulfur. Here, we present an analysis of the dependence of Arabidopsis growth on the concentration of sulfate in the growing medium with the aim of providing evidence on how plants optimize growth at a given sulfate availability. Results revealed that short-term (72 h) exposure to a broad range of Cd concentrations (0.1, 1 and 10 µM) inhibited plant growth but did not produce any significant effects on the growth pattern of both shoots and roots in relation to the external sulfate. Conversely, long-term (22 days) exposure to 0.1 µM Cd significantly changed the pattern of fresh weight accumulation of the shoots in relation to the external sulfate, without affecting that of the roots, although their growth was severely inhibited by Cd. Moreover, under long-term exposure to Cd, increasing the sulfate external concentration up to the critical value progressively reduced the inhibitory effects exerted by Cd on shoot growth, indicating the existence of sulfate-dependent adaptive responses protecting the shoot tissues against Cd injury. Transcriptional induction of the high-affinity sulfate transporter genes (SULTR1;1 and SULTR1;2) involved in sulfate uptake by roots was a common adaptive response to both short- and long-term exposure to Cd. Such a response was closely related to the total amount of nonprotein thiols accumulated by a single plant under short-term exposure to Cd, but did not showed any clear relation with thiols under long-term exposure to Cd. In this last condition, Cd exposure did not change the level of nonprotein thiols per plant and thus did not alter the nutritional need for sulfur. In conclusion, our results indicate that long term-exposure to Cd, although it induces sulfate uptake, decreases the capacity of the Arabidopsis roots to efficiently absorb the sulfate ions available in the growing medium making the adaptive response of SULTR1;1 and SULTR1;2 “per se” not enough to optimize the growth at sulfate external concentrations lower than the critical value.